Web-Based Brader Barbershop Service Application - Sumantri, Bagas; Triana, Yaya Sudarya; Maesaroh, Siti (Journal Collabits, 2025)
The development of information technology has been widely implemented in various types of businesses, both businesses in the sale of products and businesses in the service sector, in order to facilitate the work process. The design of the barbershop service application aims to help manage the service process in the barbershop location area. Based on researchers' observational data, the condition of the barbershop which has many customers every day has service constraints in the queue of orders and payment transactions at the barbershop. This results in loss of customer time as well as from employees and barbershop owners. From this problem, we need a service application that is expected to minimize the density of customer queues in ordering services and payments. The analysis and design of this application aims to help the owner of the barbershop in serving customers, using structured system development (SDLC) modeling that has limits or scope of research that starts from the planning to the design stage, namely the application interface design. So this research can produce customer service application designs that can help solve customer queue service problems.